Kajian Ketahanan Kejut Beton Ringan Serat Alumunium Dengan Agregat Alwa - Yanuar Haryanto (Dinamika Rekayasa, 2006)
This research was aimed to know the addition of alumunium fiber influence to the impact resistance of lightweight concrete. In this research, lightweight concrete was made from cement, water, sand, ALWA (Artificial Lightweight Aggregate) and Superplasticizer, mix design method was Dreux-Corrise Method. The speciment was plate with 20 cm diameter and 4 cm high. Variation of alumunium fiber addition was 0%, 0,35%, 0,75% and 1% cement weight. The test was done after 28 days age of speciment. The result showed that the most significant increasing of impact resistance was obtained on 0,75% alumunium fiber addition, which was 250% for first crack and 300% for failure